Association analysis of five candidate genes with plant height and dry matter yield in perennial ryegrass. Issue 4 (4th June 2015) - Statkevičiūté, Gražina; Aleliūnas, Andrius; Kemešyté, Vilma; Pašakinskiené, Izolda; Lübberstedt, Thomas; Brazauskas, Gintaras; Rognli, O. A.
Abstract Five candidate genes LpIAA1, LpRUB1, LpBRI1, LpSHOOT1 and LpTB1 with putative function in plant architecture were allele sequenced in a panel of 96 diploid perennial ryegrass genotypes of diverse origin. The total length of the non‐redundant genomic DNA alignment was 5425 bp and revealed 270 polymorphic sites in total. A negative significant Tajima's D value was detected in LpTB1 gene, suggesting selection pressure for low‐frequency alleles in this gene. All 96 genotypes were evaluated for plant height and dry matter yield over two years. Marker–trait associations were calculated between polymorphic sites and both phenotypic traits. Three indels and three single nucleotide substitutions in LpTB1 gene were significantly (P < 0.05, q < 0.05) associated with plant height, while one indel was associated with dry matter yield. The results suggest putative role of LpTB1 gene in plant height determination in perennial ryegrass and provide means for target allele selection.